Assessment of water quality in agricultural systems in Candipuro, Lumajang Regency, East Java, Indonesia - Hani, Evita Soliha; Alfarisy, Fariz Kustiawan; Widuri, Laily Ilman; Soeparjono, Sigit; Muhlison, Wildan; Saputra, Tri Wahyu; Yulianto, Roni (Journal of Degraded and Mining Lands Management, 2024)
The current challenges of industrial agriculture focus on environmental safety. Water quality is an indicator of environmental sustainability. The cultivation system has an impact on water quality. The aim of this study is to assess the water quality of agricultural systems. Anthropogenically, agricultural activities have an impact on environmental aspects. Identification of agricultural systems is clustered into organic and non-organic agriculture. The agricultural system in Indonesia is regulated based on SNI 6729;2016. Water sampling was carried out at three points, including upstream, middle (irrigation), and downstream (river). Water sampling at each point was repeated three times. Assessment of the physical quality of water using the Combo Quality Meter. Water samples for chemical and biological analysis at the Environmental Laboratory, Perum. Jasa Tirta 1. Determination of water quality standards refers to Government Regulation No. 82 of 2001. In the upstream section, pollution can be seen in the biological oxygen demand (BOD) indicator, with an average of 15.03 mg L-1 for organic and conventional systems. The phosphate indicator averaged 1.96 mg L-1. In the middle section (irrigation), the pollution indicators for BOD, phosphate, and total Coliform parameters were 6.76 mg L-1 for the organic system, 7.37 mg L-1 for the non-organic system, and 1,290 CFU mL-1. In the downstream (river), pollution indicators consist of total suspended solids (TSS), BOD, chemical oxygen demand (COD), and total Coliform. Anthropogenic identification for clustering agricultural systems at the research location uses stratified disproportional sampling. The results of this research provide recommendations for water quality management for sustainable agricultural environmental management.